Analysis of the floristic differences and the different soil types of roads AM 330 and AM 363, in silves and Itapiranga, Amazonas - Abreu, Nádia Rafaela Pereira de; Vieira, Antonio Fábio Sabbá Guimarães (Geosaberes; Vol 10 No 21 (2019): May - AugustDO - 10.26895/geosaberes.v10i21.720, 2019)
The main objective of this study was to describe the differences in vegetation typologies in the city of Silves-Amazonas and their relationship with the soil type, around the AM-330 and AM-363 highways. In the field it was observed that the landscape of Silves is composed of two main types of vegetation: the Ombrófila Densa and Campinarana. Thus, the research was carried out from the bibliographical survey related to the area, field research for characterization of vegetation and soil, laboratory activity for analysis and interpretation of satellite images and treatment of soil samples. The results showed that the predominantvegetation is the Ombrófila Densa, which develops mainly on the Yellow Latosol and, secondarily, the Campinarana vegetation, which develops on the Spodosol. In the area with occurrence of Latosol, the occupation is more intense and the development of gullies has been perceived. In the other two soil classes, occupation is on a smaller scale and there was no development of gullies.